Here is the 2nd one which asks to simplify the whole thing as a logarithm. Again, not sure how to take the integers at the end and convert them into log form. Thanks.
We know that $\displaystyle log_a(a) = 1$
Note that $\displaystyle 2log_2(8) = 6$ because$\displaystyle 8=2^3$
$\displaystyle 2log_4(y) = log_4(y^2)$
$\displaystyle -6+3 = -3$
As $\displaystyle -3 = log_4(4^{-3})$ (see the rule above)
So overall we can rewrite it as $\displaystyle log_4(x)+log_4(y^2)+log_4 \left(\frac{1}{64}\right)$
You can then combine the logs to give:
$\displaystyle log_4 \left(\frac{xy^2}{64}\right)$